EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN PROBLEM BASED LEARNING (PBL) DENGAN PENDEKATAN SAINTIFIK PADA MATERI OPERASI ALJABAR DITINJAU DARI GAYA BELAJAR SISWA SMP KELAS VIII DI KABUPATEN KARANGANYAR - Apri Winar Cahyani; Budiyono Budiyono; Budi Usodo (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aim of this research was to know the effect of learning models on mathematics achievement viewed from the learning style. The learning models compared were Numbered Heads Together, Problem Based Learning, and classical with saintific approach (NHT, PBL, Classical). This research was a quasi experimental with the factorial design of 3×3. The population of this research was all of students in second  grade of Junior High Schools of Karanganyar regency in academic year 2014/2015. The samples of the research consisted of 245 students and were gathered through stratified cluster random sampling. The instruments consisted of  pre test, test of learning achievement and learning style questionnaire. Hypotheses testing was performed using two-way analysis of variance with unbalanced cells. Based on the results of hypotheses testing, it were concluded as follows. 1) NHT and PBL learning models gave the same mathematics achievement. Both learning models give a better mathematics learning achievement than classical model. 2) Students with visual and auditory learning style have better mathematics achievement than students with kinesthetic ones. On the other hand, students with visual and auditory learning style have equal mathematics learning achievement. 3) On all learning models, cooperative learning NHT type, problem based learning, and classical models, students with visual learning style have an equal mathematics learning achievement with auditory. Both learning style have a better mathematics learning achievement than kinesthetic ones, (4) On all visual, auditory and kinesthetic learning style, cooperative learning with NHT type gives an equal  mathematics learning achievement with PBL. Both learning models give a better mathematics learning achievement than classical model.Keywords: Numbered Heads Together, Problem Based Learning, learning style, Scientific Mathematics learning achievement